Natural Gas Geochemistry of Jurassic Shaximiao Formation in the Western Sichuan Basin, China: Fault-Controlled Differentiation in Accumulation Process - Dong, Jun; Li, Shubing; Ye, SuJuan; Li, Qing; Wu, Changrong (Frontiers in Earth Science, 2022)
The Jurassic Shaximiao Formation in Western Sichuan has contributed significantly to the natural gas reserves and production of China, with many gas fields discovered successively. The accumulation evolution progress and discrepant gathering law are continuously improved with the constantly deepened exploration and development. In order to find evidence for the difference in gas accumulation and the method to reshape the migration and accumulation of natural gas and their dynamic processes based on time and space, this paper analyzes the dynamic accumulation process of the Middle Jurassic Shaximiao reservoir in the Zhongjiang gas field using the geochemical parameters, including the conventional composition of natural gas, light hydrocarbon components, carbon isotope, and formation water, of more than 160 natural gas samples from 155 wells. The results show that the natural gas filling period, migration patterns, phase state, etc. of the Shaximiao Formation are closely related to the distance between the hydrocarbon source faults. The geochemistry tracer parameters of natural gas and formation water reveal abundant information of the accumulation process. The Sha-3 gas reservoir, featuring a two-period hydrocarbon supply, has two migration patterns, seepage and diffusion, with the phase dominated by the water-soluble phase. Similarly, The Sha-2 gas reservoir, featuring a late single hydrocarbon supply, has the same two migration patterns, with the phase dominated by the miscible phase of water-soluble phase and free phase. The main migration pattern of the Sha-1 reservoir, which features a late single hydrocarbon supply, is seepage, with the phase dominated by the free phase. From the lower part of the Sand-3 gas reservoir to the upper part of the Sha-1 gas reservoir, the natural gas exhibits a trend where the early-late continuous filling turns into late single filling, the lateral migration distance of oil and gas becomes shorter gradually, and the gas-rich range of the gas reservoir decreases gradually. The results of this paper can provide a valuable reference for gas reservoirs controlled by faults and river sand bodies.